Valorisation of cheese whey as substrate and inducer for recombinant protein production in E. coli HMS174(DE3). (December 2019) - Hausjell, Johanna; Miltner, Martin; Herzig, Christopher; Limbeck, Andreas; Saracevic, Zdravka; Saracevic, Ernis; Weissensteiner, Julia; Molitor, Christian; Halbwirth, Heidi; Spadiut, Oliver
Abstract: Every year worldwide around 190 million tons of cheese whey are generated resulting in a huge environmental burden. We recently published a study where we showed that E. coli strain HMS174(DE3) can be cultivated using only lactose as C-source and inducer. Motivated by the results we investigated using a concentrated whey feed instead of the lactose feed. Spray drying whey and dissolving the powder allowed preparation of a 40-fold concentrated whey containing 91% lactose and 81% protein of the original whey. Cultivations using the concentrated whey feed instead of a defined lactose feed revealed 39% higher growth rates, 24% higher biomass yields and even higher specific product titers for the model enzymes, flavanone 3-hydroxylase and chalcone 3-hydroxylase. Our strategy simultaneously provides a cheap substrate for large-scale production of technical enzymes and an excellent opportunity for cheese whey valorization, reducing the biological burden resulting from whey wastewaters. Graphical abstract: Unlabelled Image Highlights: 40-fold whey concentration by spray drying and dissolving the obtained powder. Concentrated whey as C-source and inducer for recombinant protein production. Physiological parameters on the concentrated whey feed. Higher specific productivity on the whey feed compared to a defined lactose feed.